HUMAN vs. ROBOT: THE APPLICATION OF SMART TECHNOLOGY IN THE HOTEL INDUSTRY - Raditya Nafisa Purnomo Putri; Ringkar Situmorang; Amit Mehrotra (Management Study Program, Faculty of Business and Economics, Petra Christian University, 2023)
The current use of robotics, artificial intelligence, and service automation (RAISA) illustrated that innovation developed very quickly and had an enormous impact on how consumers use tourism services. This study aimed to determine how tourism and hospitality employees dealt with the pandemic, particularly when implementing the protocol called physical distance in the new normal era. This study also intended to discover our hospitality industry's readiness to confront a new normal era by applying technology to serve guests. This study conducted semi-structured interviews with 15 stakeholders. The findings indicated that the government and hotel management exploit this occurrence to enhance service quality, explicitly emphasizing hotel consumer comfort and safety. It was posited that the issues associated with the interaction between humans and robots extend beyond budgetary considerations, readiness, and maintenance. A crucial aspect to consider was robots' potential replacement of service uniqueness, particularly in developing countries. Integrating robotics and artificial intelligence (AI) inside the hotel industry may need to reevaluate the hospitality and tourism education curriculum.